FGF19 and FGF21 serum concentrations in human obesity and type 2 diabetes behave differently after diet- or surgically-induced weight loss. Issue 3 (June 2017) - Gómez-Ambrosi, Javier; Gallego-Escuredo, José M.; Catalán, Victoria; Rodríguez, Amaia; Domingo, Pere; Moncada, Rafael; Valentí, Víctor; Salvador, Javier; Giralt, Marta; Villarroya, Francesc; Frühbeck, Gema
Summary: Background & aims: Fibroblast growth factor 19 (FGF19) and 21 (FGF21) have emerged as key regulators of energy homeostasis. Our aim was to analyze the impact of weight loss (WL) induced either by conventional dietary treatment (CDT) or bariatric surgery on FGF19 and FGF21 concentrations. Furthermore, the diverse effect of sleeve gastrectomy (SG) versus RYGB (Roux-en-Y gastric bypass) as two surgical procedures that affect the gastrointestinal anatomy and physiology differently was also analyzed. Methods: Serum concentrations of FGF19 and FGF21 were measured in 137 obese patients with different degrees of insulin resistance matched by sex, age and body adiposity and compared to 33 lean individuals. Furthermore, FGF19 and FGF21 were measured in 114 subjects before and one-year after WL induced either by CDT (n = 28), SG (n = 20) or RYGB (n = 66). Results: Circulating serum FGF19 concentrations were decreased ( P  < 0.01) similarly in obese patients regardless of their degree of insulin resistance, while FGF21 levels were increased in obesity ( P  < 0.01), being further increased in obesity-associated T2D ( P  < 0.01). FGF19 concentrations were increased in obese subjects after surgically-induced WL ( P  < 0.01), but not after WL achieved by CDT, while FGF21 levels were reduced after CDT- ( P  < 0.05) or SG-induced WL ( P  < 0.05), but not after RYGB. The change in FGF21 concentrations emerged as a significant predictor of the change in insulin resistance (HOMA) after WL. Conclusions: Based on the circulating concentrations and their subsequent pattern of response following WL, we conclude that FGF19 levels are mainly related to body adiposity, in particular visceral adiposity, while FGF21 is mainly related to glucose homeostasis. ClinicalTrials.gov identifier: NCT01572090 . Highlights: FGF19 levels decreased in obese patients regardless the degree of insulin resistance. FGF21 levels increased in obesity, being further increased in obesity associated T2D. FGF19 increased after surgically-induced WL, but not after WL achieved by diet. FGF21 levels were reduced after diet or SG-induced WL, but not after RYGB. FGF21 change is a significant predictor of the change in insulin resistance after WL.